The first universities Studium generale and the origins of university education in Europe - Pedersen, Olaf (Cambridge University Press, 1997)
This is a general study of the development of higher education in Europe from antiquity until the end of the Middle Ages, set against a background of the social and political history of the period. It shows how the slender traditions of ancient learning, kept alive in the monastic and cathedral schools, was enriched by an enormous influx of knowledge from the Islamic world and how in consequence the schools developed into universities. These early institutions are examined from a variety of points of view, as institutions, as places where ideas spread and as points of interaction with local and national authority. Special attention is paid to early intellectual history and to the scientific disciplines and to the everyday life of the students and their teachers. The book is intended as a broad introduction to the subject for students of the history of education, but it will also attract general readers with only a slight knowledge of the subject